2016
DOI: 10.1007/s10935-016-0454-3
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Connectedness and Its Relation to Mental Wellness for First Nations Youth

Abstract: We explored the interrelationships among components of cultural connectedness (i.e., identity, traditions, and spirituality) and First Nations youth mental health using a brief version of the original Cultural Connectedness Scale. Participants included 290 First Nations youth (M = 14.4) who were recruited from both urban and rural school settings in Saskatchewan and Southwestern Ontario. We performed a confirmatory factor analysis of the Cultural Connectedness Scale-Short Version (CCS-S) items to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 29 publications
2
77
0
Order By: Relevance
“…AI/AN early adolescents reported significantly less school belongingness, and although we were unable to test for causal relationships because these were cross sectional analyses, feeling less connected to the school system may be related to depression and anxiety or vice versa. Although cultural connectedness was not assessed in this study, previous research has found that cultural connectedness was positively associated with school belongingness (Snowshoe, Crooks, Tremblay, & Hinson, 2016). We also found that AI/AN early adolescents reported more perceived racial discrimination than non-Hispanic Whites, and this level was similar to other racial/ethnic minorities.…”
Section: Discussionmentioning
confidence: 92%
“…AI/AN early adolescents reported significantly less school belongingness, and although we were unable to test for causal relationships because these were cross sectional analyses, feeling less connected to the school system may be related to depression and anxiety or vice versa. Although cultural connectedness was not assessed in this study, previous research has found that cultural connectedness was positively associated with school belongingness (Snowshoe, Crooks, Tremblay, & Hinson, 2016). We also found that AI/AN early adolescents reported more perceived racial discrimination than non-Hispanic Whites, and this level was similar to other racial/ethnic minorities.…”
Section: Discussionmentioning
confidence: 92%
“…The youth also learned through the seasons that change is a natural part of life, and therefore, in the face of change and difficulties, they have to adapt and move on to accomplish a goal. Overall, then, this exploration builds on and can inform strengths-based work in the area of urban Indigenous youth well-being and resilience [67,68].…”
Section: Discussionmentioning
confidence: 98%
“…As a result, population and community-based health researchers have explored resilience promoting factors beyond the individual level, to consider from a social ecological perspective these different levels and youth-environment interactions [22, 46-49, 51, 70]. Similarly, Indigenous-specific resilience research have also explored resilience-building process that emphasized the importance of culture, identity, community, family, spirituality, and Indigenous worldviews as integral factors that enhances resilience [18,48,67,68]. Although we do not deny the individual role of these resilience factors in facilitating better health and wellbeing of youth [51], it remains important to not only understand the intersecting relationships among these individual, structural, and social factors involved in resilience, but also to examine the relatively unexplored areas of Indigenous youth meaning-making connections to "land" or nature within urban contexts and how they can also play a role in supporting resilience and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…2 (Boomsma, 1982;Green, 1984). Model fit as well as model comparison were conducted; as expected, and as found in Snowshoe et al (2015Snowshoe et al ( & 2017, the three-factor There were two items that did not have significant factor loading. Item 10: "I plan on trying to find out more about my Native/Indigenous culture, such as history, Tribal identity, traditions, customs, art and language (.281)."…”
Section: Cultural Connectedness Scale-california (Ccs-ca)mentioning
confidence: 74%
“…ineffectiveness of many Western modalities in reducing health and social disparities for Indigenous communities (Tucker et al, 2016;Walters & Mohammed et al, 2011;McCormick, 1995). Given this, restoration and reconnection to the strengthening of culture or Indigenous/Native identity, is an important part of the solution (Chandler & Lalonde, 1998;Chandler, 2014;Coser, Sittner, Walls, & Handeland, 2018;Gone, 2009;Snowshoe et al, 2017;Snowshoe et al, 2015). However, a paradigm shift in the dominant culture is also needed.…”
Section: Resultsmentioning
confidence: 99%